Stories, memories and territories: reflections on methodologies in the collective construction of neighborhood stories in Montevideo (+E: University Extension Journal, 2024)
The intention of this article is to problematize the methodology for approaching neighborhood history developed in comprehensive experiences at the University of the Republic. In that sense, they develop the theoretical dimensions that organize our view and the techniques deployed to address the diverse collective memories that emerge in the territories investigated. On the one hand, we start from the perspective of integrality that seeks to generate processes of knowledge production socially relevant from dialogues of knowledge, and from there we problematize around the dimensions methodologies and techniques used in these processes. On the other hand, we integrate a perspective interdisciplinary that attempts to bring historical and anthropological disciplines into dialogue to enhance the intersections between memory, history and territorialities.
Keywords: integrality of university functions; collective memories; neighborhood stories; qualitative methodologies; territorialities